(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1989)
The megafauna recovered from the Lower Pliocene sequence at Capo S. Marco (Sinis Peninsula) are analysed; detailed studies concern taxonomy, stratigraphy and paleoecology.